## The problem

Click to see the original problem

Why cant the system expand on this question?

## Answer provided by our tutors

The web solver is not designed to solve equations from forth degree.

The best suggesting is to factor the expression:

(x^2+x)^2-8(x^2+x)+12

This way you get:

(x^2+x)^2-8(x^2+x)+12 = (x - 2)(x - 1)(x + 2)(x + 3)

Click here to see the step by step factorization.

Thus, solving (x^2+x)^2-8(x^2+x)+12 = 0 means solving (x - 2)(x - 1)(x + 2)(x + 3) = 0

This means that (x^2+x)^2-8(x^2+x)+12 = 0 if any of its factors equals zero:

x - 2 = 0, that is, x1 = 2

x - 1 = 0, that is, x2 = 1

x + 2 = 0, that is, x3 = -2

x + 3 = 0, that is, x4 = -3

And, these are the exact same solutions that the solver returns: